(untitled) (International Conference on Economics, Finance, Banking and Management, 2025)
This thesis discusses the concept of a green economy as a sustainable development model that balances economic growth with environmental protection. It analyses global trends using the 2022 Green Growth Index and focuses on Uzbekistan’s efforts to develop a green economy through policy reforms and state-backed financing. The role of state institutions in promoting renewable energy, efficiency, and environmental protection is emphasized.